Gaoju Mao Zedong sixiang weida hongqi - chedi za lan fangeming xiuzheng zhuyi wenyi luxian
'Hold high the great red banner of Mao Zedong Thought - thoroughly smash the rotting counterrevolutionary revisionist line in literature and the arts. Printno. T8081.9989.